(untitled) (Research, Society and Development, 2020)
Organic foods are products originated from techniques that exclude any use of artificial inputs such as pesticides and chemical fertilizers. It should be noted that Brazil stands out as a major consumer of various types of pesticides, substances related to the incidence of various diseases. Therefore, the search for healthier food has boosted the market for organic products. Few studies are available regarding the level of knowledge of the population, consumption and the profile of consumers of these foods in the country. Therefore, the objective of this work was to carry out a diagnosis to verify the scenario of commercialization, consumption and potential consumers of organic food in the municipality of Sete Lagoas / MG. The collection of information took place through the application of a structured questionnaire previously elaborated with established questions. The questionnaire was applied randomly to a total of 115 people attending free markets and supermarkets. It was found that 77,6% responded to know what an organic food is. However, when asked about what an organic food is, 51.6% failed to have a correct definition. Of the 77,6% only 56,3% said they gave preference to the consumption of organic foods over traditional ones. Poor accessibility to purchase was the most cited category, with 37.0% of respondents reporting that points of purchase and distribution channels are still restricted in Sete Lagoas. Followed by the high price categories (32.6%), lack of varieties (13.0%) and consumers’ lack of knowledge about the scope of their benefits (13.0%). Among the interviewees, there was a lack of knowledge and also difficulty in knowing whether they are actually purchasing an organic product. Therefore, the need for better dissemination and information is emphasized so that the population really knows what they are, how to identify and which producers and / or establishments are accredited for the production and / or commercialization of organic food.